Comparison of active tuberculosis occurrence associated with Janus kinase inhibitors and biological DMARDs in rheumatoid arthritis - Jin-Won Kwon; Yun-Kyoung Song; Jaehee Lee; Junwoo Jo (RMD Open)
Objectives This study aimed to evaluate the risk of tuberculosis associated with the use of Janus kinase (JAK) inhibitors or biological disease-modifying antirheumatic drugs (bDMARDs) in patients diagnosed with rheumatoid arthritis (RA) in South Korea.Methods In this nationwide matched-cohort study, we retrospectively identified adult patients with new-onset RA from the National Health Insurance Service database who were prescribed bDMARDs or JAK inhibitors and recently underwent latent tuberculosis infection (LTBI) screening during 2012‒2021, and followed them up until the end of 2022 for the development of active tuberculosis. HRs were estimated using Cox proportional hazards regression in a propensity score-matched cohort.Results Among 16 760 matched patients with RA (3352 JAK inhibitor users and 13 408 bDMARD users), 18.8% received tuberculosis preventive therapy for LTBI. Overall, JAK inhibitor users had a significantly lower risk of tuberculosis than bDMARD users (HR (95% CI)=0.37 (0.22 to 0.62)). Among the patients treated for LTBI, patients with low treatment adherence had a significantly higher risk than those without LTBI (HR (95% CI)=2.78 (1.74 to 4.44)). Patients without LTBI and using JAK inhibitors had a significantly lower risk of tuberculosis across all ages and sexes compared with bDMARD users.Conclusion Patients with RA using JAK inhibitors have a significantly lower risk of active tuberculosis than bDMARD users in South Korea; however, patients with RA having LTBI are equally at risk regardless of the treatment received (JAK inhibitor vs bDMARD). Therefore, vigilant tuberculosis monitoring, especially in patients with low adherence to tuberculosis preventive therapy, is essential.